Exergy efficiency optimization of photovoltaic and solar collectors' area in buildings with different heating systems. (April 2022) - Nikolic, D.; Skerlic, J.; Radulovic, J.; Miskovic, A.; Tamasauskas, R.; Sadauskienė, J.
Abstract: Exergy as a measure of useful work can be used in the design, simulation and performance evaluation of different energy systems. In this paper it is investigated the Serbian residential building with photovoltaics and solar collectors on the roof, and with three different heating systems: electrical heating, district heating and central heating with gas boiler. Exergy optimization was performed with the aim to determine the optimal area of the PV array and solar collectors on the roof (including embodied exergy). With these values, the maximum exergy efficiency of installed solar systems is obtained, and building primary energy consumption is minimized. The residential buildings with variable temperature in domestic hot water system, variable PV cell efficiency and variable hot water consumption are investigated in order to achieve positive-net energy building. The buildings were simulated in EnergyPlus software and Genopt was used for software execution control during optimization. The obtained results show that positive-net energy building with optimally sized photovoltaics and solar collectors', can be achieved in a case of gas heating system, and in the cases of PV cell efficiency of 14% and 16%. Also, an environmental and economic analysis of the most favourable solutions from exergetic optimization was performed. Total CO2 emission (with embedded emissions of CO2 ) increases with increasing amount of generated energy – for PV system of cell efficiency of 12%, 14% and 16%, total CO2 emission of solar systems is 20.8 kg CO2 /m 2, 23.5 kg CO2 /m 2 and 26.2 kg CO2 /m 2, respectively. The emission payback time decreases with increasing PV cell efficiency from 1.11 to 1.04 years. With the increase of PV cell efficiency, there is an increase in the annual financial profit (from 1518 to 4305 €), while at the same time, the investment payback period decreases (from 16.9 to 6.1 years). Best results are obtained for the building with gas heating system. Highlights: Exergy efficiency optimization of photovoltaic and solar collectors in order to determine fraction of PV panels on the roof. Minimizing primary energy consumption and achieving the Positive net-energy building. Variable: hot water temperature, PV cell efficiency and hot water consumption. Environmental analysis of solar systems. Financial profit and investment payback period of solar system.